Changed outcomes of fetuses with congenital heart disease. Issue 8 (August 2015) - Fesslova', Vlasta; Brankovic, Jelena; Boschetto, Chiara; Masini, Annaclaudia; Prandstraller, Daniela; Perolo, Antonella; Ventriglia, Flavia; Macerola, Silvia; Crepaz, Roberto; Romeo, Cristina; De Luca, Francesco; Previtera, Agata; et al.
<x xml:space="preserve">Abstract</x> Objectives To analyse the outcomes of fetuses with congenital heart disease between 2000 and 2005 in comparison to a previous multicentre study regarding the period 1983–1996. Participants and methods Data of seven centres were prospectively collected, the inclusion criteria being a confirmed fetal diagnosis after birth or at autopsy and a known follow-up, for at least 6 months after birth. Data of 649 fetuses, median age at diagnosis 24 weeks' gestation (15–37), 340/649 (52.4%) diagnosed before 24 weeks, were analysed. Results Sixty seven and 59 cases had chromosomal or extracardiac anomalies (10.3 and 9.1%). Termination of pregnancy was chosen in 21.6% of cases versus 28.9% in the previous study, being significantly lower in cases with early diagnosis (P <0.001). Out of 509 fetuses continuing pregnancy, 23 died in utero (4.5%) and 110 (21.1%) postnatally, versus 43% in the previous study (P <0.0017). Total surgical/postprocedure death occurred in 20.6% (59/287 infants) versus 37% previously (P <0.003), 67 infants being premature and 35 with associated chromosomal or extracardiac anomalies. The current overall mortality rate was higher in cases with chromosomal or extracardiac anomalies (59.5 and 51.35%, respectively, whereas it was 20.1% in isolated congenital heart disease). Overall current survival was 376 of 509 (73.9%) versus 45% in the previous study (P <0.0001). Conclusion Our data show a reduced overall and surgical mortality, with respect to our previous study, resulting from resulting from an improved perinatal management and treatment of affected fetuses in the more recent era.